Cancer as a Metaphor. (3rd April 2019) - Potts, Amanda; Semino, Elena
ABSTRACT: Since the publication of Susan Sontag's highly influential Illness as Metaphor in 1978, many studies have provided follow-up analyses on her critique of metaphors for cancer, but none have investigated her claims about the uses and implications of cancer as a metaphor (e.g., the cancer of corruption ), and her prediction that medical advances would make this metaphor obsolete. In this article, we present the first systematic study of cancer as a metaphor in contemporary English. We show the forms, frequencies, and functions of 925 metaphorical uses of cancer-related vocabulary in two large English language corpora, and discuss their implications for: (a) the framing of the phenomena that are most frequently described as cancers and of potential courses of action to be taken in relation to these phenomena; (b) perceptions of cancer itself; and (c) theoretical accounts of what makes a metaphor successful, in terms of its effectiveness and its applicability to a wide range of topics. In this way, we provide detailed evidence, and additional nuance, for Sontag's critique of cancer as a metaphor and put forward an explanation for the current persistence of this metaphor, despite its controversial status.